Aktivitas Dakwah Islam melalui Kegiatan Liqo dan Dampak terhadap Perilaku Keagamaan Masyarakat di Kp. Nyalindung Kelurahan Ciumbuleuit Kota Bandung - Siti Aisah; Komarudin Shaleh (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. This da'wah is a way to convey the goodness of Islamic teachings to the community. However, the impact felt by the community from the da'wah activities was still lacking in their religious behavior. On this basis, this researcher focuses on